Madness in Post-war American Literature - Svitavský, Otakar (Univerzita Pardubice, 2019)
This diploma thesis focuses on the theme of madness in the work of Joseph Heller, Kurt Vonnegut, and Ken Kesey. The first part of the second chapter examines how the relationship between madness and society has developed over time. The second part of the second chapter concentrates on the socio-political context of post-war America. Subsequently, the theme of madness is analysed in three selected novels.
Šílenství v americké poválečné literatuře
Keywords: poválečná Amerika; literatura; šílenství; bláznovství; společnost; post-war America; literature; madness; insanity; society